2022
DOI: 10.1111/his.14783
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: HEG1 and claudin‐4 staining will allow a diagnosis of epithelioid and biphasic mesothelioma versus non‐small‐cell lung carcinoma with only two stains in most cases

Abstract: Hypothesis: HEG1 and claudin-4 staining will allow a diagnosis of epithelioid and biphasic mesothelioma versus non-small-cell lung carcinoma with only two stains in most cases Separation of mesothelioma from metastatic carcinoma requires immunohistochemical support, with small batteries of stains recommended as a startingpoint, but these numbers commonly expand to 10, 12 or more stains, a process that is not only expensive but frequently generates anomalous or confounding results, leading to even more stains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It is often suggested that one should start with two mesothelioma and two carcinoma markers, but in practice this is not what happens: I reviewed 100 consecutive consultation cases and found that the median number of markers employed was nine; in some cases as many as 30 stains were used, and 93% of the cases had more than four stains applied 42 . What often happens is that some of the staining results are contradictory, and then even more stains are applied!…”
Section: Utility Of Heg1/claudin‐4 Immunohistochemical Staining For S...mentioning
confidence: 99%
See 4 more Smart Citations
“…It is often suggested that one should start with two mesothelioma and two carcinoma markers, but in practice this is not what happens: I reviewed 100 consecutive consultation cases and found that the median number of markers employed was nine; in some cases as many as 30 stains were used, and 93% of the cases had more than four stains applied 42 . What often happens is that some of the staining results are contradictory, and then even more stains are applied!…”
Section: Utility Of Heg1/claudin‐4 Immunohistochemical Staining For S...mentioning
confidence: 99%
“…The proposition to be discussed here in summary form is that a combination of HEG1 (clone SKM9‐2) and claudin‐4 fulfils these requirements. The interested reader is referred to Churg & Naso 42 for full details.…”
Section: Utility Of Heg1/claudin‐4 Immunohistochemical Staining For S...mentioning
confidence: 99%
See 3 more Smart Citations